Knowledge, Attitude, and Psychological Impacts of COVID-19 in Saudi Arabia - Alanazi, Naif; Bahjri, Khaled (Frontiers in Public Health, 2022)
Background: The world has been facing an unprecedented pandemic of COVID-19 with over 240 million people infected and millions of deaths. This required an enormous communication effort response from governments, international, and individuals to keep the public informed about the outbreak. When a pandemic affects communities, individuals’ knowledge and attitude are important factors to contain the outbreak. Thus, the purpose of this study is to measure individuals’ knowledge and attitude toward COVID-19 and ascertain whether a need exists for mental health services for those who were affected by the pandemic. Method: A cross-sectional design was used to measure the knowledge and attitudes about the pandemic among the Saudi population. Research participants were recruited using a snowball sampling technique through the social media platform WhatsApp. The survey for this paper was generated using Qualtrics® XM software, Version 2020. Results: A modest level of knowledge was found among the Saudi population sampled about the COVID-19 pandemic, and satisfactory knowledge about its preventive measures. Anxiety and stress existed among study population and mental health services needed during the pandemic. Conclusion: There is a need to increase awareness and provide continuous updates regarding the pandemic situation. Promoting access to mental health services is critical, as well as finding creative and suitable strategies to deliver mental health services to those who need them.